The local wisdom and land use of paddy field in Sukarame Village, Cisolok Sub-district, Sukabumi Regency - Astrid Damayanti; Alisya Zhafira Hafiz; Aninda Ainun Mi’raj; Muhammad Refiansyach Dwiyanto; Ravidania Auni (Universitas Negeri Malang, 2020)
Local wisdom is an understanding of a culture that has been inherited in a place from generation to generation by word-of-mouth. Indonesia, which still adheres to agriculture, always involves local wisdom in the use of their lands. Land-use is a visualization of the earth's surface cover, which results in a various earth formation, both natural and human-made. In the Village of Sukarame, there was a representative of Kasepuhan, which came from the Banten Kidul indigenous community, namely Kasepuhan Ciptagelar. This community still adheres to the traditional farming methods until now. The purpose of this study was to determine the relationship between land use and local wisdom from an indigenous population that lives in the Village of Sukarame. The methodology carried out in this study was a qualitative descriptive method by conducting an interview, field observation, and documentation. The data used in this study include High-Resolution Satellite Imagery from BIG (2018) and questionnaires. The analysis was also carried out in a qualitative descriptive manner. The result of the research indicates that there’s a relationship between paddy fields and the tradition of Ciptagelar in the Village of Sukarame. The distribution of paddy fields and the culture of Ciptagelar are characterized by the type of paddy, which are the ones harvested once a year with a local variety. The location of those paddy fields is only located in the Hamlet of Lebak Lengsir and Hamlet of Pamokoan, whose communities still adhere to the tradition of Ciptagelar.